Information management and skills development of Peruvian students during virtual education - Chalco-Fernández, Julio César (2022)
The objective of this essay is to analyze some issues related to the responsibilities of both teachers and parents and that were decisive for the mishandling and control of information by Peruvian students, resulting in serious problems in the school. development of educational skills during the pandemic period. For which, we have raised some ideas that will help us explain the problem. First of all, it is not possible to replicate the achievements of face-to-face education in distance education. On the other hand, the information offered by the Internet is important for the development of skills, but its use requires adequate guidance and control: or that, given their age, students tend to immediacy and reject the most elaborate work (the same thing happens with information management) and that. definitely there is a shared responsibility between parents and teachers, regarding this problem. Finally, we analyze a contradiction: when the digital divide was high, students had access to reliable physical information; now that it has been shortened, access to information is greater, but also, the risks are greater. The most important conclusion we reached is that we are more than convinced that the misuse and handling of information during this distance education has been decisive in the mediocre academic performance and other problems in the development of skills in the areas of education. of the Peruvian basic education system.